Method for preparing ultrafine-diameter high-performance mesophase pitch-based carbon fiber and product

By using the three-step method to prepare mesophase bitumen and combining the extruder and mesh belt furnace process, the problem of ultra-fine diameter carbon fiber breaking wire during the heat treatment process is solved, and the preparation of high-performance mesophase bitumen-based carbon fiber is realized, reducing production costs and improving applicability.

CN119640439APending Publication Date: 2025-03-18TONGCHUAN TIANCE NEW MATERIAL TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411954186.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

In the prior art, the tension drawing of ultrafine diameter carbon fibers can easily cause a large number of wire breaks during heat treatment, and graphitization requires strict equipment and processes, resulting in the inability to carry out long-term large-scale production.

Method used

The mesophase asphalt is prepared by three-step method, melt-spinning is performed by extruder and two-stage cooling is performed under an inert environment to reduce the wire breakage during the spinning process of the primary wire. Then, the high-temperature carbonization process is eliminated, and pre-oxidation and low-temperature carbonization are used to adopt a mesh belt furnace, and finally graphitization is carried out to obtain ultra-fine diameter high-performance mesophase asphalt-based carbon fibers.

Benefits of technology

By controlling the fine-graining of the spinning process, the filament breakage phenomenon is reduced, production costs are reduced, and the fibers have excellent comprehensive performance and stronger applicability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119640439A_ABST
    Figure CN119640439A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of novel macromolecular carbon materials, in particular to a method for preparing ultrafine-diameter high-performance mesophase pitch-based carbon fibers and a product, and the method comprises the following steps: preparing low-viscosity high-purity mesophase pitch by adopting a three-step method; adopting a melt extrusion spinning process to prepare mesophase pitch-based protofilament fibers; a pre-oxidation process; a mesh belt furnace process is adopted in the low-temperature carbonization process; graphite treatment; and carrying out electrolytic washing and sizing reel treatment. The mesophase pitch with low viscosity and high purity is prepared by adopting a three-step method, so that fine-diameter spinning is facilitated, and the fine-diameter yarn breakage condition is controlled; two sections of cooling gas are added, so that the defects that a spinneret is easy to cool and cannot be drafted for a long distance in the fine-diameter spinning process are overcome, and the situations that the fiber strength is reduced and the diameter is not uniform are avoided; the mesh belt furnace is used for pre-oxidation and low-temperature carbonization treatment, the high-temperature carbonization process is omitted, graphitization treatment is directly carried out, the risk that fine-diameter fibers are low in strength and prone to breaking in the carbonization process is avoided, and the broken filament amount and the abrasion process are reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of novel polymer carbon materials, and in particular relates to a method for preparing ultra-fine diameter high-performance mesophase asphalt-based carbon fibers and products. Background Art

[0002] Asphalt-based graphite fiber filament is a high-performance fiber material made from asphalt raw materials through fine processing. It undergoes a series of complex processes such as spinning, pre-oxidation, carbonization and graphitization, and finally forms graphite fibers with excellent properties such as high strength, high modulus, high electrical conductivity and high thermal conductivity. This fiber is not only lightweight but also resistant to high temperature and corrosion, so it is widely used in many fields such as aerospace, sporting goods, electronics, and construction.

[0003] Application No. 2018101359062 discloses an intermittent and continuous method for preparing asphalt-based graphite fiber filaments, which uses intermittent pre-oxidation and intermittent low-temperature carbonization, and continuous high-temperature carbonization and graphitization. Since the asphalt-based pre-oxidized filament loses about 36% of its own weight in the low-temperature carbonization process, the fiber components and structures will undergo significant changes in such a large weight loss, so tension drawing is required to suppress the disorder of fiber orientation due to weight loss, and the pre-oxidized filament will produce a large amount of waste gas and tar during the low-temperature carbonization process, and the tension drawing of ultra-fine diameter carbon fiber during the heat treatment process is prone to cause a large number of broken filaments, and the spinning process has relatively high requirements for the fluidity of the raw materials, and the technical indicators of the intermediate phase asphalt raw materials are difficult to achieve. In addition, the graphitization of ultra-fine diameter carbon fibers has strict requirements on equipment and processes. In mass production, the graphite furnace heating element often fails, resulting in the stop of the entire production line, and long-term large-scale production cannot be carried out. Summary of the invention

[0004] In order to solve the problem in the prior art that ultrafine diameter carbon fibers are prone to a large number of broken fibers due to tension drawing during heat treatment, the present invention aims to provide a method and product for preparing ultrafine diameter mesophase asphalt-based carbon fibers.

[0005] Technical solution: The present invention provides a method for preparing ultra-fine diameter mesophase pitch-based carbon fibers, comprising the following steps: A method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fibers comprises the following steps: Step 1: Using petroleum residue as raw material, a three-step method is used to prepare mesophase asphalt; Step 2: melt-spinning the prepared mesophase asphalt in an extruder and passing through two cooling zones under an inert environment to obtain mesophase asphalt-based raw fibers; Step 3: pre-oxidizing the mesophase asphalt-based raw fibers in a mesh belt furnace to obtain mesophase asphalt-based pre-oxidized fibers; Step 4: subjecting the mesophase pitch-based pre-oxidized fibers to low-temperature carbonization in a mesh belt furnace to obtain mesophase pitch-based low-carbon fibers; Step 5: graphitizing the mesophase pitch-based low carbon fiber to obtain an ultra-fine diameter high-performance mesophase pitch-based carbon fiber product; Step six: subjecting the ultra-fine diameter high-performance mesophase asphalt-based carbon fiber product to electrolytic water washing, sizing and winding treatment to obtain a rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber product.

[0006] Preferably, in step 1, the preparation method of mesophase asphalt is as follows: The first step is the positive pressure stage, with a reaction temperature of 380-460°C, a reaction time of 4-6 hours, a reaction pressure of 4-6 MPa, and a nitrogen atmosphere; In the second step, the material after the first step reaction is purged with nitrogen at normal pressure, the reaction temperature is 340-380°C, and the reaction time is 4-6h; In the third step, the material after the second step reaction is transported to the extruder for deashing and purification. The extruder is set with three temperature zones at 190~310℃.

[0007] Preferably, in step 1, the viscosity of the mesophase asphalt under the test condition of 310°C is 180-280 Pa·s, and the softening point is 260-290°C.

[0008] Preferably, in step 2, the aspect ratio of the spinneret is (1-3):1, the diameter of the spinneret hole is 0.15-0.3 mm, and the number of the spinneret holes is 1-2K.

[0009] Preferably, in step 2, the spinning temperature in the extruder melt spinning is 290-310°C, the inert environment is provided by an inert gas, the cooling zones at both ends are respectively the first cooling zone and the second cooling zone, the first cooling zone is located at the outlet of the spinneret, the distance between the second cooling zone and the outlet of the spinneret is 3-15 mm, the temperature of the first cooling zone is 220-280°C, and the temperature of the second cooling zone is 25-50°C; the diameter of the intermediate phase asphalt-based raw silk fiber is 9-11 μm, and the fiber specification is 1K.

[0010] Preferably, in step three, during the pre-oxidation treatment, the temperature is 180-300° C., the gas atmosphere is air, and the flow rate of the air through the fiber in the furnace is 1.5-3 m / s.

[0011] Preferably, in step 4, during the low-temperature carbonization treatment, the gas atmosphere is high-purity nitrogen with a purity of more than 99.8%, the low-temperature carbonization temperature is 350-1000°C, and the oxygen content in the furnace is less than 3ppm.

[0012] Preferably, in step five, during the graphitization treatment, the temperature zones are divided into 3 to 4, the graphitization atmosphere is high-purity argon, the graphitization temperature is 2200 to 2800°C, the wire drawing is a positive drawing of 1 to 3%, and the wire speed is 4 to 6 m / min.

[0013] Preferably, in step six, during the electrolytic water washing process, ammonium bicarbonate or ammonium bisulfate is used as the electrolyte, and deionized water is used in the water washing process; during sizing, the concentration of the sizing agent is 1-3%.

[0014] A product obtained according to the method for preparing ultrafine diameter high-performance mesophase asphalt-based carbon fiber, the product has a mechanical tensile strength of 2.5GPa to 3.3GPa, a tensile modulus of 800GPa to 1000GPa, an elongation at break greater than 0.25%, a sizing rate of 1% to 3%, and a fiber diameter of 5 to 7μm.

[0015] Compared with the prior art, the present invention has the following significant advantages: The method for preparing ultra-fine diameter mesophase pitch-based carbon fibers of the present invention can control the diameter thinning during the spinning process, reduce the disadvantage that the fine diameter original fibers are severely broken due to curing and cannot be drawn over long distances, and the prepared mesophase pitch-based carbon fibers have a diameter of 5 to 7 μm, and the high-temperature carbonization process is omitted during the process, the cost is low, and the fiber has excellent comprehensive performance. Specifically: The mesophase asphalt is prepared and purified by a three-step method to obtain a mesophase asphalt with low viscosity, good fluidity, high purity and good spinnability. Compared with the traditional process, the negative pressure reaction process is reduced, and the extruder reaction is used as the deashing and purification process. The process is simple and controllable, low cost and more applicable; and the low viscosity and good fluidity are more suitable for the spinning process of ultra-fine diameter mesophase asphalt raw fibers; During the spinning process, two cooling zones are added at the spinneret, and the highest temperature of the first cooling zone is set basically close to the spinning spinneret temperature. Compared with the traditional process, the cooling and solidification time of the ultra-fine diameter mesophase asphalt precursor when it leaves the spinneret is increased, and the phenomenon of stress shrinkage and structural damage of low-strength precursor fibers during rapid solidification is slowed down, reducing the breakage of the precursor during spinning and ensuring the uniformity of the product diameter. The mesh belt furnace process is used for the pre-oxidation process and the low-temperature carbonization process, and the high-temperature carbonization process is omitted. Compared with the traditional production process, the risk of fiber breakage caused by transitional friction in the continuous line due to the difficulty in controlling the degree of oxidation of the fiber, the rapid oxygen penetration, and the low strength of the low-carbon process are reduced, so that the ultra-fine diameter carbon fiber has better mechanical properties and structural integrity in the pre-oxidation and low-temperature carbonization process; The graphitization treatment temperature zone is zoned and positive pulling is used for continuous line routing. Compared with the traditional process, the graphitization treatment temperature zone zoning can more effectively exert the excellent properties of the material itself. The use of positive pulling routing changes the fiber wrinkles and poor appearance of the ultrafine diameter mesophase asphalt-based fibers caused by shrinkage during pre-oxidation and low-temperature carbonization, and changes the fiber orientation from the fiber structure, making the ultrafine diameter mesophase asphalt-based carbon fibers have better thermal conductivity and mechanical properties. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 A flow chart of a method for preparing ultra-fine diameter mesophase pitch-based carbon fibers according to the present invention; Figure 2 This is a hot stage photo of the mesophase pitch prepared in Example 1 of the present invention; Figure 3 This is a scanning electron microscope cross-section of the ultra-fine diameter high-performance mesophase asphalt-based carbon fiber prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0017] The embodiments of the present invention are further described below in conjunction with the accompanying drawings: like Figure 1 As shown, the present invention discloses a method for preparing ultra-fine diameter mesophase pitch-based carbon fiber, comprising the following steps: Step 1: Using petroleum residue as raw material, a three-step method is used to prepare low-viscosity and high-purity mesophase asphalt; the first step is a positive pressure stage, the reaction temperature is 380-460°C, the reaction time is 4-6h, the reaction pressure is 4-6MPa, and the atmosphere is nitrogen; the second step is to purge the material after the first step reaction with normal pressure nitrogen, the reaction temperature is 340-380°C, the time is 4-6h, the third step is to transport the material after the second step reaction to an extruder for deashing and purification treatment, the extruder is set at three temperature zones at 190-310°C for material extrusion, the extruder deashing zone is set at 270-300°C, and the mesophase asphalt with a viscosity value of 180-280 Pa·s and a softening point of 260-290°C under the test condition of 310°C is obtained; Step 2: The mesophase asphalt is melt-spun in an extruder, the spinneret aspect ratio is (1-3):1, the spinneret hole diameter is 0.15-0.3mm, and the number of spinnerets is 1-2K; after passing through two cooling zones under an inert environment, a mesophase asphalt-based precursor fiber is obtained. Among them, the spinning temperature in the melt spinning out of the machine is 290-310°C, the inert environment is provided by an inert gas (such as nitrogen), and the two cooling zones are sequentially arranged at the spinneret, the first cooling zone is located at the spinneret hole outlet, the distance between the second cooling zone and the spinneret hole outlet is 3-15mm, the temperature of the first cooling zone is 220-280°C, and the temperature of the second cooling zone is 25-50°C, and a mesophase asphalt-based precursor fiber with a diameter of 9-11μm and a fiber specification of 1K is obtained.

[0018] Step 3: pre-oxidizing the mesophase asphalt-based raw fiber in a mesh belt furnace, the pre-oxidation temperature is 180-300°C, the gas atmosphere is air, the air is preheated, the temperature is 25°C-35°C, the flow rate of the air through the fiber in the furnace is 1.5-3 m / s, and the mesophase asphalt-based pre-oxidized fiber is obtained; Step 4: subjecting the mesophase pitch-based pre-oxidized fiber to low-temperature carbonization treatment in a mesh belt furnace, wherein the gas atmosphere during the carbonization process is high-purity nitrogen with a purity of more than 99.8%, the low-temperature carbonization temperature is 350-1000°C, 6-8 temperature zones are set, a waste discharge zone is set, and the temperature zone of the waste discharge zone is set to 500-650°C, the oxygen content in the furnace is less than 3ppm, and a mesophase pitch-based low carbon fiber is obtained; Step 5: graphitizing the mesophase asphalt-based low carbon fiber, the temperature zone of the graphitization treatment is divided into 3 to 4, the graphitization atmosphere is high-purity argon, the graphitization temperature is 2200 to 2800°C, the wire drawing is positive drawing 1 to 3%, and the wire drawing speed is 4 to 6 m / min, to obtain a high-performance fine-diameter mesophase asphalt-based carbon fiber product; Step six: The fine-diameter mesophase asphalt-based carbon fiber products are successively electrolyzed and washed. The electrolyte is ammonium bicarbonate or ammonium bisulfate with a concentration of 15-25%. Deionized water is used in the washing process. The sizing agent concentration is 1-3%. Finally, a constant tension winding process is performed to obtain a rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber product.

[0019] Example 1 Step 1: The petroleum residue is transported to the reactor through a material delivery pump, and after nitrogen replacement and airtightness detection are completed, the temperature is started to rise, and the first positive pressure stage is carried out. The temperature is 440°C and the reaction time is 4h. After the reaction is completed, the temperature is lowered to 380°C, and the second step of normal pressure nitrogen purging is started. The reaction is 4h. After the reaction is completed, the material heat is discharged to the extruder material storage area, and the third step of extruder deashing and purification treatment is carried out. The temperature zone of the extruder is set to 200°C, 250°C, and 300°C. The extruder deashing zone is set at 300°C. After the extruder is finished, the intermediate phase asphalt is prepared to obtain Figure 2 Hot stage photograph of mesophase pitch; Step 2: Install a spinneret with an aspect ratio of 1:1, a spinneret hole diameter of 0.15 mm, and a spinneret hole number of 1K, select the mesophase asphalt with a viscosity of 260 Pa·s and a softening point of 260°C under the test condition of 310°C obtained in step 1, crush the mesophase asphalt, and transport it to a screw extruder through a hopper for melt spinning. The spinneret passes through two nitrogen cooling zones, and the distance between the two cooling gases is adjusted to 3 mm. The temperature of the first nitrogen cooling zone is 260°C, and the temperature of the second nitrogen cooling zone is 50°C. After the precursor is oiled, dried and rolled up, a mesophase asphalt-based precursor fiber with a diameter of 10 μm is obtained; Step 3: The mesophase asphalt-based raw silk fiber obtained in step 2 is unwound by a wire unwinding machine, and the mesophase asphalt-based raw silk is pre-oxidized in a mesh belt furnace. The pre-oxidation temperature is 180-280°C, the heating rate is 2°C / min, the gas atmosphere is air, the air is preheated, the temperature is 30°C, and the flow rate of air through the fiber in the furnace is 1.5m / s, to obtain the mesophase asphalt-based pre-oxidized fiber; Step 4: subjecting the mesophase asphalt-based pre-oxidized fiber obtained in step 3 to low-temperature carbonization treatment in a mesh belt furnace, wherein the gas atmosphere during the carbonization process is high-purity nitrogen, the low-temperature carbonization temperature zone is set to 350°C, 450°C, 550°C, 650°C, 750°C, 850°C, and 1000°C, a waste discharge zone is set, and the waste discharge zone temperature zone is set to 650°C, the oxygen content in the furnace is less than 3ppm, and a fine-diameter mesophase asphalt-based low-carbon fiber is obtained; Step 5: The fine-diameter mesophase asphalt-based low carbon fiber obtained in step 4 is graphitized, the graphitization atmosphere is high-purity argon, the graphitization temperature is set to 2200°C, 2400°C, 2600°C, and 2800°C, the wire drawing is 1.5% positive drawing, and the wire speed is 4m / min, to obtain a high-performance fine-diameter mesophase asphalt-based carbon fiber product; Step six: The fine-diameter mesophase asphalt-based carbon fiber products obtained in step five are electrolyzed and washed successively. Ammonium bicarbonate is used as the electrolyte with a concentration of 15%. Deionized water is used in the washing process. The sizing agent concentration is 3%. Finally, constant tension winding treatment is performed to obtain rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber products.

[0020] Attached Figure 2 It can be reflected that the mesophase asphalt prepared by this process has a content of 100%, has a wide-area streamlined structure, and has good fluidity. Figure 3 The final product prepared by this process has a good structural orientation, a fully radiation split structure, and a fiber diameter of 5 to 8 microns.

[0021] The average performance of the ultrafine mesophase pitch-based carbon fiber obtained in Example 1 is: when the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 300m, the mechanical tensile strength is 3143MPa, the tensile modulus is 944GPa, the elongation at break is 0.33%, and the diameter is 6.43μm. When the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 350m, the mechanical tensile strength is 2970MPa, the tensile modulus is 962GPa, the elongation at break is 0.31%, and the diameter is 6.47μm.

[0022] Example 2 Step 1: The petroleum residue is transported to the reactor through a material delivery pump, and after nitrogen replacement and airtightness detection, the temperature is increased, and the first positive pressure stage is carried out, the temperature is 450°C, the reaction time is 3.5H, and the reaction pressure is 5-6Mpa. After the reaction is completed, the temperature is lowered to 360°C, and the second step of normal pressure nitrogen purging is started, and the reaction is carried out for 4.5H. After the reaction is completed, the material heat is discharged to the extruder material storage area, and the third step of extruder deashing and purification treatment is carried out. The temperature zone of the extruder is set to 200°C, 250°C, and 300°C, and the extruder deashing zone is set at 290°C. The intermediate phase asphalt is prepared after the extruder is finished; Step 2: Install a spinneret with an aspect ratio of 1:1, a spinneret diameter of 0.15 mm, and a spinneret number of 1K, select the mesophase asphalt with a viscosity of 280 Pa·s and a softening point of 275°C under the test condition of 310°C obtained in step 1, crush the mesophase asphalt, and transport it to a screw extruder through a hopper for melt spinning. The spinneret passes through two nitrogen cooling zones, and the distance between the two cooling gases is adjusted to 4 mm. The temperature of the first nitrogen cooling zone is 280°C, and the temperature of the second nitrogen cooling zone is 50°C. After the precursor is oiled, dried and rolled up, a uniform diameter thin-diameter mesophase asphalt-based precursor fiber is obtained, and the precursor diameter is 11 μm; Step 3: The fine-diameter mesophase asphalt-based precursor fiber obtained in step 2 is unwound by a de-filament machine, and the mesophase asphalt-based precursor is pre-oxidized in a mesh belt furnace. The pre-oxidation temperature is 180-275°C, the heating rate is 2°C / min, the gas atmosphere is air, the air is preheated, the temperature is 30°C, and the flow rate of air passing through the fiber in the furnace is 1.5m / s, so as to obtain a fine-diameter mesophase asphalt-based pre-oxidized fiber; Step 4: subjecting the fine-diameter mesophase asphalt-based pre-oxidized fibers obtained in step 3 to low-temperature carbonization in a mesh belt furnace, wherein the gas atmosphere during the carbonization process is high-purity nitrogen, the low-temperature carbonization temperature zones are set to 320°C, 480°C, 600°C, 700°C, 800°C, 900°C, and 1000°C, a waste discharge zone is set, the waste discharge zone temperature zone is set to 600°C, the oxygen content in the furnace is less than 3ppm, and a fine-diameter mesophase asphalt-based low carbon fiber is obtained; Step 5: The fine-diameter mesophase asphalt-based low carbon fiber obtained in step 4 is graphitized, the graphitization atmosphere is high-purity argon, the graphitization temperature is set to 2200°C, 2450°C, 2650°C, 2750°C, the wire drawing is positive drawing 2%, and the wire speed is 4m / min, to obtain a high-performance fine-diameter mesophase asphalt-based carbon fiber product; Step six: The fine-diameter mesophase asphalt-based carbon fiber products obtained in step five are electrolyzed and washed successively. Ammonium bicarbonate is used as the electrolyte with a concentration of 15%. Deionized water is used in the washing process. The sizing agent concentration is 3%. Finally, constant tension winding treatment is performed to obtain rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber products.

[0023] The average performance of the ultrafine mesophase pitch-based carbon fiber obtained in Example 2 is: when the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 300m, its mechanical tensile strength is 2382MPa, the tensile modulus is 953GPa, the elongation at break is 0.25%, and the diameter is 7.12μm. When the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 350m, its mechanical tensile strength is 2787MPa, the tensile modulus is 953GPa, the elongation at break is 0.29%, and the diameter is 7.21μm.

[0024] Example 3 Step 1: The petroleum residue is transported to the reactor through the material delivery pump, and after nitrogen replacement and airtightness detection, the temperature is started to rise, and the first positive pressure stage is carried out, the temperature is 460°C, the reaction time is 3H, and the reaction pressure is 5-6Mpa. After the reaction is completed, the temperature is lowered to 375°C, and the second step of normal pressure nitrogen purging is started, and the reaction is carried out for 5H. After the reaction is completed, the material heat is discharged to the extruder material storage area, and the third step of extruder deashing and purification treatment is carried out. The temperature zone of the extruder is set to 200°C, 250°C, and 300°C, and the extruder deashing zone is set at 300°C. The intermediate phase asphalt is prepared after the extruder is finished; Step 2: Install a spinneret with an aspect ratio of 1:1, a spinneret diameter of 0.15 mm, and a spinneret number of 1K, select the mesophase asphalt with a viscosity of 275 Pa·s and a softening point of 265°C under the test condition of 310°C obtained in step 1, crush the mesophase asphalt, and transport it to a screw extruder through a hopper for melt spinning. The spinneret passes through two nitrogen cooling zones, and the distance between the two cooling gases is adjusted to 8 mm. The temperature of the first nitrogen cooling zone is 275°C, and the temperature of the second nitrogen cooling zone is 50°C. After the precursor is oiled, dried and rolled up, a mesophase asphalt-based precursor fiber with a diameter of 11.3 μm is obtained; Step 3: The mesophase asphalt-based raw silk fiber obtained in step 2 is unwound by a wire unwinding machine, and the mesophase asphalt-based raw silk is pre-oxidized in a mesh belt furnace. The pre-oxidation temperature is 180-280°C, the heating rate is 2°C / min, the gas atmosphere is air, the air is preheated, the temperature is 35°C, and the flow rate of air passing through the fiber in the furnace is 1.5m / s, to obtain the mesophase asphalt-based pre-oxidized fiber; Step 4: subjecting the mesophase asphalt-based pre-oxidized fiber obtained in step 3 to low-temperature carbonization treatment in a mesh belt furnace, wherein the gas atmosphere during the carbonization process is high-purity nitrogen, the low-temperature carbonization temperature zone is set to 350°C, 500°C, 650°C, 800°C, and 950°C, a waste discharge zone is set, and the waste discharge zone temperature zone is set to 600°C, the oxygen content in the furnace is less than 3ppm, and a mesophase asphalt-based low carbon fiber is obtained; Step 5: The mesophase asphalt-based low carbon fiber obtained in step 4 is graphitized, the graphitization atmosphere is high-purity argon, the graphitization temperature is set to 2300°C, 2650°C, and 2800°C, the wire drawing is 1.5% positive drawing, and the wire speed is 4m / min, to obtain a high-performance fine-diameter mesophase asphalt-based carbon fiber product; Step six: The fine-diameter mesophase asphalt-based carbon fiber products obtained in step five are electrolyzed and washed successively. Ammonium bicarbonate is used as the electrolyte with a concentration of 15%. Deionized water is used in the washing process. The sizing agent concentration is 3%. Finally, constant tension winding treatment is performed to obtain rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber products.

[0025] The average performance of the ultrafine mesophase pitch-based carbon fiber obtained in Example 3 is: when the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 300m, the mechanical tensile strength is 2517MPa, the tensile modulus is 970GPa, the elongation at break is 0.26%, and the diameter is 7.16μm. When the length of the rolled ultrafine diameter high-performance mesophase pitch-based carbon fiber product is 350m, its mechanical tensile strength is 2542MPa, the tensile modulus is 917GPa, the elongation at break is 0.27%, and the diameter is 7.43μm.

[0026] Table 1 is a summary of the performance of ultra-fine diameter mesophase pitch-based carbon fibers in Examples 1 to 3

[0027] The content of the present invention is not limited to the embodiments listed, and any equivalent changes made to the technical solution of the present invention by ordinary technicians in this field after reading the description of the present invention are covered by the claims of the present invention.

Claims

1. A method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fibers, characterized in that: The following steps are involved: Step 1: Using petroleum residue as raw material, a three-step method is used to prepare mesophase asphalt; Step 2: melt-spinning the prepared mesophase asphalt in an extruder and passing through two cooling zones under an inert environment to obtain mesophase asphalt-based raw fibers; Step 3: pre-oxidizing the mesophase asphalt-based raw fibers in a mesh belt furnace to obtain mesophase asphalt-based pre-oxidized fibers; Step 4: subjecting the mesophase pitch-based pre-oxidized fibers to low-temperature carbonization in a mesh belt furnace to obtain mesophase pitch-based low-carbon fibers; Step 5: graphitizing the mesophase pitch-based low carbon fiber to obtain an ultra-fine diameter high-performance mesophase pitch-based carbon fiber product; Step six: subjecting the ultra-fine diameter high-performance mesophase asphalt-based carbon fiber product to electrolytic water washing, sizing and winding treatment to obtain a rolled ultra-fine diameter high-performance mesophase asphalt-based carbon fiber product.

2. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to claim 1, characterized in that: In step 1, the preparation method of mesophase asphalt is as follows: The first step is the positive pressure stage, with a reaction temperature of 380-460°C, a reaction time of 4-6 hours, a reaction pressure of 4-6 MPa, and a nitrogen atmosphere; In the second step, the material after the first step reaction is purged with nitrogen at normal pressure, the reaction temperature is 340-380°C, and the reaction time is 4-6h; In the third step, the material after the second step reaction is transported to the extruder for deashing and purification. The extruder is set with three temperature zones at 190~310℃.

3. The method for producing ultra-fine diameter high-performance mesophase pitch-based carbon fibers according to claim 1, characterized in that: In step 1, the viscosity of the mesophase asphalt is 180-280 Pa·s under the test condition of 310°C, and the softening point is 260-290°C.

4. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to claim 1, characterized in that: In step 2, the aspect ratio of the spinneret is (1-3):1, the diameter of the spinneret hole is 0.15-0.3 mm, and the number of the spinneret holes is 1-2K.

5. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to claim 1, characterized in that: In step 2, the spinning temperature in the extruder melt spinning is 290-310°C, the inert environment is provided by an inert gas, the cooling zones at both ends are respectively the first cooling zone and the second cooling zone, the first cooling zone is located at the spinneret outlet, the distance between the second cooling zone and the spinneret outlet is 3-15 mm, the temperature of the first cooling zone is 220-280°C, and the temperature of the second cooling zone is 25-50°C; the diameter of the intermediate phase asphalt-based raw silk fiber is 9-11 μm, and the fiber specification is 1K.

6. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to claim 1, characterized in that: In step three, during the pre-oxidation treatment, the temperature is 180-300°C, the gas atmosphere is air, and the flow rate of air passing through the fiber in the furnace is 1.5-3 m / s.

7. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fibers according to claim 1, characterized in that: In step 4, during the low-temperature carbonization treatment, the gas atmosphere is high-purity nitrogen with a purity of more than 99.8%, the low-temperature carbonization temperature is 350-1000°C, and the oxygen content in the furnace is less than 3ppm.

8. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fibers according to claim 1, characterized in that: In step five, during the graphitization treatment, the temperature zones are divided into 3 to 4, the graphitization atmosphere is high-purity argon, the graphitization temperature is 2200 to 2800°C, the wire drawing is positive drawing 1 to 3%, and the wire speed is 4 to 6 m / min.

9. The method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to claim 1, characterized in that: In step six, during the electrolytic washing process, ammonium bicarbonate or ammonium bisulfate is used as the electrolyte, and deionized water is used in the washing process; during sizing, an epoxy sizing agent is used as the sizing agent with a concentration of 1-3%.

10. A product obtained by the method for preparing ultra-fine diameter high-performance mesophase pitch-based carbon fiber according to any one of claims 1 to 9, characterized in that: The mechanical tensile strength of the product is 2.5GPa~3.3GPa, the tensile modulus is 800GPa~1000GPa, the elongation at break is greater than 0.25%, the sizing rate is 1%~3%, and the fiber diameter is 5~7μm.